Influence of cultural predispositions on consumer behaviour in the UK - Král, David (2022)
The aim of this thesis is to analyse the impact of cultural tendencies on consumer behaviour in the British cultural environment. The author uses Hofstede’s Cultural Dimensions theory to demonstrate the uniqueness of British cultural tendencies and then benchmarks it to Dutch and Ukrainian cultural tendencies. Next, the author investigates the communication of a few selected companies in two product categories in all three cultural environments. The author performs a comparative analysis of collected secondary data to determine if their communication strategies align with the local cultural tendencies. The outcome of this analysis provides a set of possible opportunities for improvement of their communication strategies. The thesis also produces a set of recommendations for companies selling or aiming to sell goods and services in the British cultural environment.